Examining weight concern and delay discounting in adolescent females. (April 2016) - Thamotharan, Sneha; Lange, Krista; Ramos, Ashley; Fields, Sherecce
Abstract: Objective: Pediatric obesity is a growing public health concern that contributes to high rates of negative long-term physical and mental health outcomes. Research focused on identifying risk for pediatric obesity has linked delay discounting, or an inclination for immediate rewards, as well as weight concern to individuals with greater Body Mass Index (BMI). The current study seeks to fill a void in the literature by examining how these two variables interact to promote higher BMI in female adolescents. Method: Adolescent ( n = 60) females between the ages of 13–19 years ( m age = 17.45, SD = 1.74) of age completed the Eating Disorder Examination Questionnaire (EDE-Q) and the Delay Discounting Questionnaire. Results: A mediation model examined whether delay discounting accounted for the relationship between weight concern and BMI. Results indicate that in the current study weight concern was negatively related to delay discounting and delay discounting was negatively related to BMI. The overall model revealed that a partial mediation occurred [b = 1.28, t(60) = 4.92, p < 0.01]. Discussion: These results suggest that while impulsivity is an important factor to consider, other constructs may also be influential in how weight concerns contribute to greater BMI. Nevertheless, the results indicate that prevention and interventions should identify females with high levels of both weight concern and impulsivity as an increased risk for experiencing pediatric obesity and long-term negative health outcomes. Highlights: We examine the relationship between weight concern and delay discounting, two correlates of BMI in pediatric populations Individuals with greater weight concern discounted more by delay Delay discounting appears to partially mediate the relationship between weight concern and BMI in adolescent females Females with greater weight concerns and whop discount more are at increased risk for pediatric obesity